The Efforts of United Nations Women in Addressing The Issue of Dowry Death in India 2019-2022 - Mitzy, Gulia Ichikaya; Maheswari, Dennise (Department of International Relations, Hasanuddin University, 2025)
The dowry traditions has been in existence for a long time and is difficult to eradicate, serving as a symbol for the bride who will become a member of her husband's family. Over time, the basic essence and amount of dowry have changed. If the groom's family is not satisfied with the dowry given, it can lead to violence or even murder. The research method used is qualitative. This study aims to find out the problem of dowry death in India and the collaboration of UN Women and the Government of India in dealing with the problem of dowry death. The Indian government has also begun to think step by step that dealing with this case is still difficult to overcome, because the patriarchal culture is still strong. This study analyzes UN Women's cooperation with NGOs to deal with the dowry death problem. In 2019-2022, dowry death cases in India have started to decrease significantly. Although there are still many women who are not brave enough to report dowry violence.